Exploring ChatGPT’s Role in Educating Patients on Community Reintegration After Spinal Cord Injury: A Mixed-Method Study - Variyani, Pallavi S.; Parekh, Sandip; Gadhavi, Bhavna (Journal of Neonatal Surgery, 2025)
Background: Community reintegration following spinal cord injury (SCI) involves navigating a complex web of physical, psychological, social, and environmental challenges. Patient education plays a critical role in this transition, yet many existing resources are either too generic or not readily accessible. The emergence of artificial intelligence tools like ChatGPT offers potential as a supplementary educational resource. Objective: This study aimed to evaluate the reliability, readability, and perceived utility of ChatGPT in delivering educational content about community reintegration after SCI, using a mixed-methods approach. Methods: In Phase I, 15 structured and clinically relevant questions were submitted to ChatGPT-4. The responses were assessed for reliability (using the DISCERN tool), readability (Flesch Reading Ease and Gunning Fog Index), and domain-specific comprehensiveness (via a custom rubric across physical, psychological, social, and environmental domains). In Phase II, semi-structured interviews were conducted with SCI patients, caregivers, and rehabilitation professionals to gather qualitative perspectives. Thematic analysis was used to explore recurring patterns. Results: ChatGPT’s responses yielded a mean DISCERN score of 3.82 ± 0.51, with an inter-rater intraclass correlation coefficient (ICC) of 0.84. Readability analysis revealed a mean Flesch score of 70.4 and a Gunning Fog Index of 9.1, suggesting accessibility for most readers. Comprehensiveness ratings were highest in physical (4.5 ± 0.5) and social (4.2 ± 0.7) domains, but relatively lower in environmental aspects (3.1 ± 0.8). Thematic analysis of interviews revealed three key themes: ease of access, surface-level adequacy, and supportive emotional tone. Conclusion: ChatGPT shows promise as a readable, moderately reliable, and emotionally supportive tool for patient education following SCI. However, its limitations in depth and individualization highlight the need for its integration under clinical guidance, rather than as a standalone solution..